HUBUNGAN KONSEP DIRI DENGAN KECEMASAN PADA MAHASISWA TINGKAT AKHIR DI INSTITUT KESEHATAN HELVETIA MEDAN TAHUN 2020 - Chairunnisa, Milna; Fadillah, Nur (Granada El-Fath, 2021)
Basically, humans are expected to be able to adapt to their environment, as well as students. Students are part of individuals who are expected to be able to perform tasks in their educational environment. These tasks are related to attendance in lectures, completing course assignments and other matters related to the teaching and learning process. The purpose isto find out the relationship between self-concept and anxiety in final year students at the Helvetia Institute of Health Medan in 2020. The research design is a quantitative study to determine the self-concept with anxiety in final year students with a cross sectional approach. The population taken in this study were 50 students at the Helvetia Institute of Health, Medan, and used total sampling. Results; with the chi square test. The results of this study indicate that of the 50 respondents at the Helvetia Health Institute, Medan, it is known that those who have a positive self-concept are the majority as many as 30 respondents (60.0%) while the majority of moderate anxiety are 15 respondents (30.0%) with a p value of 0.020.